Circ_0036490 and DKK1 competitively bind miR-29a to promote lipopolysaccharides-induced human gingival fibroblasts injury - Yeke Wu; Bin Li; Disi Deng; Hongling Zhou; Min Liu; Huangping Ai; Yilin Xin; Weihan Hua; Lixing Zhao; Li Li (Taylor & Francis Group, 2024)
AbstractMicroRNA (miRNA) plays a regulatory role in periodontitis. This study aimed to explore whether miR-29a could affect lipopolysaccharides (LPSs)-induced injury in human gingival fibroblasts (HGFs) through the competitive endogenous RNAs (ceRNA) mechanism. Periodontal ligament (PDL) tissues and HGFs were derived from patients with periodontitis and healthy volunteers. Periodontitis cell model was established by treating HGFs with LPS. Expression levels of circ_0036490, miR-29a, and DKK1 were evaluated by the reverse transcription quantitative real-time PCR (RT-qPCR) method. Western blotting assay was performed to assess protein expression levels of pyroptosis-related proteins and Wnt signalling related proteins. Cell viability was evaluated by cell counting kit-8 (CCK-8) assay. Concentration of lactate dehydrogenase (LDH), interleukin (IL)-1β, and IL-18 were determined by Enzyme-linked immunosorbent assay (ELISA). Pyroptosis rate were determined by flow cytometry assay to evaluate pyroptosis. The interaction between miR-29a and circ_0036490 or DKK1 was verified by dual-luciferase reporter and RNA pull-down assays. MiR-29a expression was lower in PDL tissues of patients with periodontitis than that in healthy group; likewise, miR-29a was also downregulated in LPS-treated HGFs. Overexpression of miR-29a increased cell viability and decreased pyroptosis of HGFs induced by LPS while inhibition of miR-29a exerted the opposite role. MiR-29a binds to circ_0036490 and elevation of circ_0036490 contributed to dysfuntion of LPS-treated HGFs and reversed the protection function of elevated miR-29a. In addition, miR-29a targets DKK1. Overexpression of DKK1 abrogated the effects of overexpressed miR-29a on cell vaibility, pyroptosis, and protein levels of Wnt signalling pathway of LPS-treated HGFs. Circ_0036490 and DKK1 competitively bind miR-29a to promote LPS-induced HGF injury in vitro. Wnt pathway inactivated by LPS was activated by miR-29a. Thence, miR-29a may be a promising target for periodontitis.